Impact of nanoparticles on double-walled carbon nanotubes, using nonlocal elasticity theory - ehsan zamani ehsan zamani; fatemeh abbaspour; sajjad seifoori (مجله مدل سازی در مهندسی, 2019)
Increasing the electrical resistance and reducing the conductivity of nanotubes due to the impact forces have attracted a lot of their use as power sensors. In this paper, the impact of a nanoparticle on simply supported and clamped double-walled nanotubes has been investigated by using elasticity nonlocal theory. The spring constant for each nanobeam, which is influenced by the geometry of the structure and its shear and bending deformations, has been obtained using mass-spring system. The results of this analytical method have been compared with the results in the background research. According to the results, by increasing the speed, the dynamic deformation in the middle of the double-walled nanobeam increases. The dynamic deformation in the double-walled nanotube is smaller than single-walled nanotube and the maximum dynamic deformation of the double-walled nanotubes is increased by increasing the mass of nanoparticle. Also by considering the van der Waals force between the layers of double-walled nanotube, maximum dynamic deformation in the middle of nanobeam reduces.